Conflitos religiosos e espaço urbano contemporâneo: cruzamentos dos fenômenos de dispersão espacial dos sistemas de significações religiosas de neopentecostais e religiões afro-brasileiras no Rio de Janeiro - Silva, Rachel Cabral da (2013)
This research focuses around the attacks of religious groups in the face of neo-Pentecostal religions african - Brazilian Umbanda and Candomble, in urban areas of Rio de Janeiro , from a geographical analysis. Actions of religious intolerance, guided Eurocentric values, prevent the manifestations of worship and african - religious as well as prevent the trajectory of socio fans of african - Brazilian religions and undermine the religious freedom of these religions , for threatening, assaulting and demonizarem the deities of african - Brazilian religions. Thus, we present the spatiality of everyday practices of the religious symbolic system african -Brazilian, which correspond to an element of identity, because it is in space that are configured forms and own shares of the social group or individual, contributing to a reading of meanings. For this it is necessary to analyze the contexts of racial and religious interactions, marked by horizontality and verticality, take a reading on the spatial embodiment of the victims of religious intolerance is to highlight the religious differences between Christians and adherents of neo-Pentecostal african - Brazilian religions, between epistemology white and the other black, and Phenomenology and concepts of Geography of Religion in providing theoretical framework to analyze and interpret the world of experience, action and values of the signs, the relationship of humans with the world and the human being with other in the world and the spatial distribution of religious phenomena. In order to illuminate these theories, we bring summaries of cases brought to the attention of the CCIR - Commission for Combating Religious Intolerance and were attended by Human Rights Organization - Legal Project, in the years 2008-2010. There are few contributions to geographical studies which allow a methodological foundation, about the Geography of Religion on conflicts arising from interactions between different religious systems, and on this ongoing project of religious homogenization that neopentencostais are imposing to each and all. The dissertation shows that systems of concrete manifestations of different religious phenomena collide in material space and compete faithful, and aims to address disputes occur as spatial dispersion of religious meanings and Neopentecostais Matrix African Religions in urban space in Rio de Janeiro. What are the consequences of these disputes? By giving visibility to academic actions which are based on these issues, we removed the african - Brazilian religion of locus of subordination, bringing the center of the debate and thereby strengthening the democratic system of law and the actions to combat religious intolerance of the CCIR.